Modeling and optimization of microwave-based bio-jet fuel from coconut oil: Investigation of response surface methodology (rsm) and artificial neural network methodology (ann) - Ong M.Y.; Nomanbhay S.; Kusumo F.; Raja Shahruzzaman R.M.H.; Shamsuddin A.H. (MDPI AG, 2023)
Ant colony optimization; Ethanol; Jet fuel; Microwave irradiation; Molar ratio; Neural networks; Sensitivity analysis; Vegetable oils; American society for testing and materials; ANN modeling; Developed model; Fuel production; Microwave power; Modeling and optimization; Renewable fuels; Response surface methodology; Combustion